Comparison between the Prebolus T1 Measurement and the Fixed T1 Value in Dynamic Contrast-Enhanced MR Imaging for the Differentiation of True Progression from Pseudoprogression in Glioblastoma Treated with Concurrent Radiation Therapy and Temozolomide Ch… - Nam, J.G.; Kang, K.M.; Choi, S.H.; Lim, W.H.; Yoo, R.-E.; Kim, J.-H.; Yun, T.J.; Sohn, C.-H. (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: Glioblastoma is the most common primary brain malignancy and differentiation of true progression from pseudoprogression is clinically important. Our purpose was to compare the diagnostic performance of dynamic contrast-enhanced pharmacokinetic parameters using the fixed T1 and measured T1 on differentiating true from pseudoprogression of glioblastoma after chemoradiation with temozolomide.MATERIALS AND METHODS: This retrospective study included 37 patients with histopathologically confirmed glioblastoma with new enhancing lesions after temozolomide chemoradiation defined as true progression (n = 15) or pseudoprogression (n = 22). Dynamic contrast-enhanced pharmacokinetic parameters, including the volume transfer constant, the rate transfer constant, the blood plasma volume per unit volume, and the extravascular extracellular space per unit volume, were calculated by using both the fixed T1 of 1000 ms and measured T1 by using the multiple flip-angle method. Intra- and interobserver reproducibility was assessed by using the intraclass correlation coefficient. Dynamic contrast-enhanced pharmacokinetic parameters were compared between the 2 groups by using univariate and multivariate analysis. The diagnostic performance was evaluated by receiver operating characteristic analysis and leave-one-out cross validation.RESULTS: The intraclass correlation coefficients of all the parameters from both T1 values were fair to excellent (0.689–0.999). The volume transfer constant and rate transfer constant from the fixed T1 were significantly higher in patients with true progression (P = .048 and .010, respectively). Multivariate analysis revealed that the rate transfer constant from the fixed T1 was the only independent variable (OR, 1.77 exttimes 105) and showed substantial diagnostic power on receiver operating characteristic analysis (area under the curve, 0.752; P = .002). The sensitivity and specificity on leave-one-out cross validation were 73.3% (11/15) and 59.1% (13/20), respectively.CONCLUSIONS: The dynamic contrast-enhanced parameter of rate transfer constant from the fixed T1 acted as a preferable marker to differentiate true progression from pseudoprogression.DCEdynamic contrast-enhancedKeprate transfer constantKtransvolume transfer constantTMZtemozolomideVpthe blood plasma volume per unit volume of tissueVethe extravascular extracellular space per unit volume of tissueAUCarea under the curve